ZCE 537/2 - Ultrasound and Magnetic Resonance Imaging [Ultrasound dan pengimejan Resonans Magnet] - February - March 2005 - PPSF, Pusat Pengajian Sains Fizik (2005)
UNTVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2004/2005 February - March 2005 ZCE 537/2 - Ultrasound and Magnetic Resonance Imaging [Ultrasound dan pengimejan Resonans Magnet] Duration: 2 hours [Masa : 2 jam]